1998
DOI: 10.1046/j.1464-410x.1998.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of lower‐pole nephrolithiasis — increasing or not?

Abstract: Objective  To determine if the incidence of lower‐pole nephrolithiasis is increasing. Methods  A previously published meta‐analysis of trends in the location of stones in the kidney, using data from 1984 to 1992, determined the percentage of lower pole stones in 26 722 kidney stones treated by extracorporeal shockwave lithotripsy (ESWL). We performed prospective studies on all patients treated by ESWL for a single renal stone (not manipulated from the ureter) in two organizations; at Lithotripters Inc., 47 303… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…This distribution has not changed during the last decades [89]. The overall results of ESWL for the management of calyceal calculi depend significantly on the localization and size of the stone [8, 13, 49, 50, 51](tables 6–8).…”
Section: Resultsmentioning
confidence: 99%
“…This distribution has not changed during the last decades [89]. The overall results of ESWL for the management of calyceal calculi depend significantly on the localization and size of the stone [8, 13, 49, 50, 51](tables 6–8).…”
Section: Resultsmentioning
confidence: 99%
“…Cass et al [6] reported an incidence of 30–36% stones treated with SWL was located in LP calyx. In general, it is recognized that small-sized calculi <1 cm are treated successfully with SWL while for larger ones >2 cm the method of choice is PNL.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is recognized that small-sized calculi <1 cm are treated successfully with SWL while for larger ones >2 cm the method of choice is PNL. Stones in the range of 1–2 cm represent an area of ongoing controversy regarding the respective roles of SWL, PNL and ureteroscopy [5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…Stagnation and retention of crystals in the inferior calyceal system due to gravity is accused for lower pole calculi. Cass et al reported that 25-35% of calyceal calculi are localized in the inferior calyceal system [10]. ESWL is the first choice therapy for the problematic lower pole stones and the same anatomical area is evaluated in many studies that examines the effects of anatomical factors on the stone clearance after ESWL.…”
Section: Discussionmentioning
confidence: 99%